Gaelic games coaches’ attitudes towards, awareness of and use of injury prevention exercise programmes - Calvin Teahan; Enda Whyte; Siobhán O’Connor (PLoS ONE, 2026)
Purpose Gaelic games (GG) are multidirectional, evasive sports with unpredictable high-intensity activity. Lower extremity injuries are common. Injury prevention exercise programmes (IPEPs) have been introduced, effectively reducing injuries and increasing neuromuscular performance. However, the awareness and use of IPEPs are anecdotally low among coaches. Methods Adult GG coaches (n = 342) completed an anonymous online survey, including awareness, use, and attitudes towards IPEPs and injury prevention. Frequencies and descriptive statistics were conducted, a chi-squared test was used to assess any differences in awareness and use of IPEPs, a Mann-Whitney U test was used to examine differences between groups for attitudes to injury prevention. Results Overall, 59.5% (n = 165) of coaches reported using any form of an IPEPs, including modified or self-developed programmes, while 44.1% of coaches (n = 130) were aware of formal IPEPs. Use was statistically higher in elite coaches than non-elite (p < 0.01, phi = 0.16). No significant differences in IPEP use were observed by coach gender, team gender, or coaching education. Many coaches developed their own IPEP or altered a current IPEP, particularly participants coaching females. Coaches had a positive attitude towards injury prevention, but 40.6% stated a lack of knowledge on how to use an IPEP, with 34.5% agreeing there was no training available to teach them. Discussion Despite generally positive attitudes towards injury prevention, awareness and implementation of formal IPEPs among GG coaches remain limited. These findings highlight the need for targeted coach education and improved dissemination strategies to enhance the adoption and effective implementation of IPEPs in GG, which is critical to mitigating the risk of injury.